2007
DOI: 10.3168/jds.2006-823
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Characteristics That Drive Consumer Liking of Butter

Abstract: This study identified and explored the sensory characteristics that drive consumer liking of butter. A trained descriptive panel evaluated 27 commercial butters using a defined sensory language. Two focus groups were conducted with butter consumers to gain an understanding of consumer use and consumption habits. Six representative butters and 2 vegetable oil spreads were selected for consumer acceptance testing. Both internal and external preference mapping techniques were applied to interpret consumer data. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 20 publications
2
72
0
1
Order By: Relevance
“…Similar results were reported by Okturk et al, 23 who reported that total FFA contents of cow cream butters increased (P<0.05) within 90d of refrigerated storage. Conversely, Krause et al 7 found that the FFA amounts were consistent until 6m of storage at 5°C. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Okturk et al, 23 who reported that total FFA contents of cow cream butters increased (P<0.05) within 90d of refrigerated storage. Conversely, Krause et al 7 found that the FFA amounts were consistent until 6m of storage at 5°C. …”
Section: Resultsmentioning
confidence: 99%
“…Sweet cream butter is commonly known to Americans which is produced with or without the addition of salt in the pasteurized, churned cream. 7 Compared to cream from cow milk, cream from goat milk has a lower melting point due to higher proportions of short-and medium-chain fatty acids such as caproic (C6:0), carprylic (C8:0) and capric (C10:0) acids. 1,2 This factor also imparts a distinctive flavor and texture characteristic to the butter from goat milk.…”
Section: Introductionmentioning
confidence: 99%
“…Samples of cheese (10 g) were presented on clear plastic Petri dishes. Butter and spread samples (1.5 g) were spread onto 4 cm × 4 cm pieces of white pita bread (Sainsbury's, London, UK) as previously described (Krause et al, 2007). Milk samples (30 mL) were presented in clear crystal polystyrene cups.…”
Section: Sample Preparation For Sensory Analysesmentioning
confidence: 99%
“…Vocabularies were developed for appearance, odor, taste, flavor, texture and mouthfeel, and aftertaste or aftereffect attributes of the dairy products in reference to published literature (Drake et al, 2001;Krause et al, 2007;Oupadissakoon et al, 2009;Tables 2, 3, and 4). Although the butter was presented on pita bread (to relate results to the consumer liking data), the panel was asked to manipulate the product in their mouths and focus only on the attributes of the butter.…”
Section: Quantitative Descriptive Analysismentioning
confidence: 99%
“…Several studies have been reported using such as methodology. Krause et al (2007) to gain an understanding of consumer use and consumption habits. Bouteille et al (2013) explored the freshness sensation of yoghurts and yoghurt-like products by means of two Focus group sessions (n=19).…”
Section: Introductionmentioning
confidence: 99%